OPAC: INNOVATION OF LIBRARY SERVICES IN THE DIGITAL ERA AT SMK NEGERI 1 SIDOARJO - Fitria Agustina , Isna; Rustianingsih , Eni; Febrianti Efendi, Salsabilla (ANTIS PUBLISHER, 2024)
Objective: This study aims to explore the implementation of an Integrated Library System through the Online Public Access Catalog (OPAC) at SMK Negeri 1 Sidoarjo, with a specific focus on the SMALDIVA Library. The research seeks to evaluate how OPAC enhances information retrieval for students and identify challenges in its practical application. Method: A descriptive qualitative approach was employed, utilizing data collection techniques such as field observation, semi-structured interviews with library staff and students, and documentation analysis. The study also reviewed supporting institutional records related to library services and system usage. Results: The findings indicate that OPAC has significantly improved the ease and speed of information access for students. However, notable challenges include limited user understanding of OPAC functionality and a shortage of library personnel with professional training in library and information science. These issues have hindered the system’s full potential. Novelty: This research provides one of the first focused assessments of OPAC implementation in a vocational high school setting in Sidoarjo. It highlights the need for systematic user training and professional development for library staff as critical components for optimizing digital library services in secondary education environments.